The Effect of Bank’s Internal Factors Towards Micro Financing in Islamic Commercial Bank at Indonesia (Journal of Islamic Economic Laws, 2018)
The main driver of Indonesian economic wheel is the small and medium-sized enterprises (SME). This SME plays significant role as well in providing employment opportunity while in the same time adding numbers of business units that support the household income from the business. One of the obstacles faced by SME is the capital and financing constraint, especially for the financing from the bank. Without financing, SME will lose its capability to grow and develop since the main support for SME is the capital and financing itself. This research aims to know the internal factors affecting the third party fund, inflation and the rate of return in the period of 2012-2014 in Islamic commercial banks at Indonesia. The research will carry out the OLS procedure since this technique allows us to know clearly the factors affecting financing in the SME. Our research shows that third party fund significantly affect SME financing with positive sign. Meanwhile, the rate of return is observed to affect negatively to the financing. Inflation also has significant and positive effect with bigger coefficient compared to others in financing for SME.